EVALUASI PENGGUNAAN ANTIBIOTIK PADA PASIEN PNEUMONIA DI RSUD DR. ADNAAN WD PAYAKUMBUH TAHUN 2019 - Lola Azyenela; Ringga Novelni (JFL : Jurnal Farmasi Lampung, 2021)
Abstrac Pneumonia is an inflammation of the lung parenchyma caused by bacteria, viruses, fungi, and parasites, but pneumonia can also be caused by chemicals or due to physical exposure such as temperature or radiation. The main therapy given to patients with pneumonia caused by bacteria is antibiotics. WHO recommends ATC (Anatomical Therapeutic Chemical) and DDD (Defined Daily Dose) as global standards for the study of drug use, one of which is antibiotics. The purpose of this study was to see an overview of the use of antibiotics using the ATC/DDD and DU 90% methods at Dr. Adnaan WD Payakumbuh Hospital in 2019. This study was a descriptive analytic study with a cross sectional design that was carried out retrospectively using data obtained from patient medical records. . Samples were taken by purposive sampling technique. The results showed that the quantity of antibiotic use from 111 patients in medical records obtained a total of 101.04 grams of DDD/100 days of hospitalization. The most widely used antibiotic was ceftriaxone and the least was cefoperazone. Antibiotics that fall into the 90% segment are Ceftriaxone (36.57%), Levofloxacin (28.39%), Cefotaxime (7.83%), Ciprofloxacin (7.40%), Cefixime (7.11%),Ceftazidime ( 6.24%) DDD/100 patient-days. Keywords: ATC/DDD, DU90%, evaluation of antibiotic use, pneumonia